Revue yougoslave - Arnaoutovitch, Alexandre, 1888-; Ligue des universitaires serbo-croato-slovènes. (Paris : Ligue des universitaires serbo-croato-slovènes, 1919)
Includes section "Bibliographie."
Eight double numbers (no. 1/2-15/16) were issued in 1919; 5 double numbers ( no. 1/2-9/10) were issued from Jan. to Oct. 1920; no. 11 was issued on Nov. 1920; no. 12 in Dec. 1920. No more published.
Keywords: Yugoslavs -- Periodicals; Yugoslavia -- Periodicals